Nitric Oxide (NO) and Arginine as Factors for Increasing Poultry Meat Productivity - Titov , Vladimir; Dolgorukova, Anna; Khasanova, Lyudmila; Kochish, Ivan; Korenyuga, Maxim (KnE Life Sciences, 2021)
Nitric oxide (NO) is intensively synthesized in the embryo of birds. There is evidence that NO mediates myogenesis at the embryonic stage. In this regard, it might be possible to control muscle development and meat productivity by modulating NO synthesis. Using high-precision and a highly sensitive enzymatic sensor, the authors found that it is not the rate of synthesis that correlates with meat productivity, but the rate of NO oxidation to nitrate, which occurs in the tissues of the embryo. In broilers, it is several orders of magnitude higher than in layers. This indicator is solely due to the characteristics of embryonic tissues and is allelically determined. In-ovo arginine supplementation, a source of NO, did not lead to a significant increase in its synthesis and oxidation, but occasionally increased live weight gain, which was likely associated with a deficiency of free arginine and was not directly related to the effect of nitric oxide. Exogenous NO donors were oxidized with the same intensity as endogenous donors. These compounds did not have a significant effect on growth rate. Also, a reduction of 50% in the rate of NO synthesis under the action of a NO synthase inhibitor did not affect this parameter. Thus, regulation of poultry meat productivity is possible by modulating gene expression related to embryonic NO oxidation and ensuring an optimal amino acid and energy equilibrium, rather than by promoting embryonic NO synthesis. Keywords: Nitric oxide (NO), NO donor compounds, nitrate, arginine, live weight